Efektivitas Pemanfaatan Kulit Bawang Merah dan Air Cucian Beras sebagai Zat Pengatur Tumbuh bagi Tanaman Tomat (Solanum lycopersicum Mill.) dalam Upaya Penyusunan Buku Petunjuk Praktikum Fisiologi Tumbuhan - Nawariah, Siti; Fajri, Siti Rabiatul; Royani, Ida (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine the effectiveness of the use of onion peel and rice washing water as growth regulators for tomato plants (Solanum lycopersicum Mill.). The research design used in this study was a completely randomized design (CRD), which consisted of 1 group with a sub-sampling pattern consisting of 5 concentrations and 5 replications, a total of 25 experimental units, with treatment design (P0, P1, P2 , P3, and P4). The research parameters include plant stem height, stem diameter and number of leaves. This research was conducted at the Green House Laboratory of the Biology Education Study Program, FSTT, Mandalika University of Education. The object of this research is the growth of tomato plants (Solanum lycopersicum Mill.). Parameters measured were stem height, stem diameter, and number of leaves of tomato plants with a period of 21, 28, 35, and 42 days after planting (DAT). Data were analyzed using Analysis of Variance (ANOVA). The results of the One Way ANOVA analysis showed that the parameter value of tomato plant stem height was 0.999 > 0.05, the analysis of the parameter value of the stem diameter was 0.929 > 0.05, and the analysis of the parameter values ​​for the number of leaves was 0.997 > 0.05, so the three tomato plant parameter data no significance or no effect (H0) is accepted. The results of the value of the validation of the practicum manual obtained values ​​with criteria suitable for use through the assessment of validator 1, namely 72%, validator 2 is 75%, and validator 3 is 79%.